Transformative space design for sex workers’ community: a case study at Lorong Haji Taib 1 and 2, Chow Kit, Kuala Lumpur - Abdul Naser, Muhammad Haziq; Abd Jalil, Nurul Amira; Azmy, Mohd Syafiq (Universiti Teknologi MARA, Perak, 2025)
Sex workers and their marginalised communities are often subjected to spatial marginalisation and stigmatisation. Confined to specific locales due to the nature of their activities, involuntary participants of this community who were forced or coerced into sex work through sex trafficking syndicates are essentially trapped. Stigma and social exclusion attached to sex work can further marginalise the sex workers' community, making it difficult for them to access essential services and support. Although there are many efforts and assistance programmes designed to help this marginalised community, it is essential to comprehend the specific spatial and typology of spaces that can best meet the complex needs and aspirations of sex workers and the community. The research aims to explore the potential role of transformative spaces and the impact of spatial design integration on the psychological needs of sex workers in Lorong Haji Taib 1 and 2, Chow Kit, Kuala Lumpur, with a focus on improving their well-being by promoting community empowerment and improved social cohesion. Analysis of data collected from literature review, case study, and unstructured interviews show the intricate interplay between the physical environment and the psychological well-being of sex workers. The findings unveil the nuanced complexities of creating spaces that address immediate needs while empowering and uplifting marginalised communities. Design recommendations for transformative spaces that could support and improve the lives of sex workers were modelled from the needs, behaviour, and daily routine of the sex workers’ community in Lorong Haji Taib 1 and 2.